Developing islamic values-based biology smart cards for the eleventh-grade students of special school - Nusa Intan Asy Syifa; Nukhbatul Bidayati Haka (JPBIO (Jurnal Pendidikan Biologi), 2021)
Students with special needs require specific education services different from other students in general. This research aims to develop Islamic value-based biology smart cards media for students with hearing and visual impairments. Furthermore, this research also seeks to determine the feasibility and effectiveness of the developed learning media in improving students' learning motivation. This research employed the research and development method (R & D) with the development procedure proposed by Borg and Gall, which consists of nine stages. The research involved three experts in validating the product: a media expert, a material expert, and a language expert. Ten students with hearing impairment and ten students with visual impairment were selected as the research subjects. The validation findings from media experts are 98.5 percent, material experts' validation results are 97.32 percent, and linguists' validation results are 98.12 percent. The findings of the paired sample t-test were 0.00 < 0.05. As a result of the product trial, it can be determined that the developed Islamic value-based biology smart card media are feasible and effective in enhancing eleventh-grade special school students' motivation with hearing and visual impairments.